How Low Is Too Low? Postpartum Hemorrhage Risk among Women with Thrombocytopenia - Carlson, Laura M.; Dotters-Katz, Sarah K.; Smid, Marcela C.; Manuck, Tracy A. (American Journal of Perinatology, 2017)
Objective To estimate the association between severity of thrombocytopenia and postpartum hemorrhage.Study Design We performed a secondary analysis of a prospective cohort of women delivering by cesarean or vaginal birth after cesarean conducted by the National Institute of Child Health and Human Development (NICHD) Maternal–Fetal Medicine Unit. Women delivering ≥ 20 weeks with platelets < 400,000/mL were included. Thrombocytopenia was defined as predelivery platelets of < 150,000/mL. Primary outcomes were (1) laboratory evidence of hemorrhage, defined as a decrease in hemoglobin ≥ 4 mg/dL and (2) clinical evidence of hemorrhage, a composite of atony, transfusion, coagulopathy, hysterectomy, laparotomy, or intensive care unit admission. Odds ratios were calculated for primary outcomes using thrombocytopenia as a dichotomous and ordinal variable.Results A total of 54,597 women were included; 5,611 (10.3%) had antepartum thrombocytopenia, 1,976 (3.6%) women had laboratory evidence of hemorrhage, and 3,862 (7.1%) had clinical evidence of hemorrhage. Thrombocytopenia was associated with both laboratory evidence of hemorrhage (adjusted odds ratio [aOR]: 1.60, 95% CI: 1.38–1.86) and clinical evidence of hemorrhage (aOR: 1.68, 95% CI: 1.52–1.83). The odds of laboratory and clinical evidence of hemorrhage increased incrementally with severity of thrombocytopenia.Conclusion Thrombocytopenia is associated with both laboratory and clinical evidence of hemorrhage; risk increases dramatically as platelet count decreases.
Keywords: postpartum hemorrhage; platelets; thrombocytopenia